Immunometabolic Changes in Glia – A Potential Role in the Pathophysiology of Obesity and Diabetes. (1st November 2020) - Robb, Josephine L.; Morrissey, Nicole A.; Weightman Potter, Paul G.; Smithers, Hannah E.; Beall, Craig; Ellacott, Kate L.J.
Graphical abstract: Highlights: Glia direct respond to changes in nutrients and hormones regulating energy balance. Microglia and astrocytes are implicated in the pathophysiology of obesity and diabetes. Obesity causes gliosis: reversible changes in glia structure and function. In metabolic disease inflammation-driven changes in glial likely regulates neurons. Glial regulation of neural circuits controlling energy balance requires more study. Abstract: Chronic low-grade inflammation is a feature of the pathophysiology of obesity and diabetes in the CNS as well as peripheral tissues. Glial cells are critical mediators of the response to inflammation in the brain. Key features of glia include their metabolic flexibility, sensitivity to changes in the CNS microenvironment, and ability to rapidly adapt their function accordingly. They are specialised cells which cooperate to promote and preserve neuronal health, playing important roles in regulating the activity of neuronal networks across the brain during different life stages. Increasing evidence points to a role of glia, most notably astrocytes and microglia, in the systemic regulation of energy and glucose homeostasis in the course of normal physiological control and during disease. Inflammation is an energetically expensive process that requires adaptive changes in cellular metabolism and, in turn, metabolic intermediates can also have immunomodulatory actions. Such "immunometabolic" changes in peripheral immune cells have been implicated in contributing to disease pathology in obesity and diabetes. This review will discuss the evidence for a role of immunometabolic changes in glial cells in the systemic regulation of energy and glucose homeostasis, and how this changes in the context of obesity and diabetes.